Performance Based Economical Design of Hybrid Filter and APFC to Improve the Power Quality of Industry - Nikum, Karuna; Wagh, Abhay; Saxena, Rakesh; Mishra, Bharat (International Journal of Engineering and Technology, 2018)
The aim of this paper to analyze the power quality (PQ) and provide a cost effective solution to mitigate the harmonics and improve the power factor (PF) in industry. The detailed harmonic analysis and monitoring performed to rectify the PQ issues. Â In this paper automatic power factor correction (APFC) for power factor improvement and hybrid power filter (HPF)which is combination of (APF) and passive Power filter (PPF) has been proposed. The design of active filter by two different control scheme has been proposed and compared. The modelling and simulation has been carried out to verify proposed analysis in MATLAB Simulink environment individually. To make the proposed solution cost-effective, combination of PPF only Â for fifth harmonic frequency and APF for other remaining harmonic frequencies has been used. The HPF reduces the cost as well as rating of the APF. The cost and rating of APF is also compared with and without passive filter of the system. Â Â